HYPERTHYROIDISM WITH SEVERE TRANSAMINITIS IN A PREGNANT FEMALE WITH A TOXIC NODULE - Naidu, Thaalitha; Azman, Siti Sanaa Wan; Ali, Masliza Hanuni Mohd; Adnan, Syuhada Dan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Hyperthyroidism occurs in 0.1–0.4% of pregnancies, mostly due to Graves’ disease. Other causes include toxic adenoma, multinodular goitre and trophoblastic tumours. CASE A 27-year-old primigravida at 9 weeks presented with vomiting, epigastric discomfort, anorexia, palpitations and weight loss of 8 kg in one month. Family history was significant for thyroid malignancy. On examination, she was alert but dehydrated, icteric and tachycardic (HR 120 bpm), spiking fever (38°C) with tremors present. No goitre or thyroid eye signs noted. Systemic findings were unremarkable. Investigations revealed TWC: 13 x10⁹/L, Urea: 8 mmol/L, Sodium: 119 mmol/L, TB: 31.5 µmol/L, ALP: 74 U/L, ALT: 943 U/L and AST: 630 U/L. ECG showed sinus tachycardia. She was managed symptomatically with anti- emetics and intravenous fluids. However, her liver function worsened; TB: 56 µmol/L, ALP: 69 U/L, ALT: 1583 U/L and AST: 530 U/L. TFT revealed thyrotoxicosis with Free T4 > 100 pmol/L and TSH 0.012 mIU/L. Neck ultrasonography showed a homogenous, non-enlarged thyroid gland with a TIRADS 5 thyroid nodule on the right. Normal vascularity was seen within the gland. Hepatic ultrasonography was unremarkable. She was initiated on oral propranolol 60 mg TDS and Lugol’s iodine 10 drops TDS for five days. Thyroid autoantibodies, viral hepatitis panel and other second-line investigations for transaminitis were negative. As results improved, she was discharged with tapered Lugol’s iodine (5 drops TDS for 5 days) and continued on propranolol. After two weeks, both liver and thyroid function normalised. Fine-needle aspiration cytology of the thyroid nodule revealed atypia of undetermined significance, Bethesda Category III. Postpartum hemi- or total thyroidectomy has been planned as she remains well with a stable pregnancy. CONCLUSION Significant transaminitis in early pregnancy mandates a broad differential, including thyroid dysfunction, as early recognition ensures favourable maternal and fetal outcomes. In selected cases, short-term iodine and beta-blockade offer a safe, effective bridge to definitive management.